2017
DOI: 10.1111/ijn.12557
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of strategies similar to the Magnet model to create positive work environments on nurse satisfaction

Abstract: This study showed that 24 months after the implementation of these strategies, nurse satisfaction with their work environment and management style increased significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…In addition to countries in North America, countries identifying workplace environment as an area of interest included, but were not limited to: Australia, Estonia, Finland, Hong Kong, Iceland, Israel, Turkey, and Taiwan. Topics addressed in selected publications included job satisfaction (Chien & Yick, 2016;Dekeyser Ganz, & Toren, 2014;Jiang et al, 2016;Kaunonen et al, 2015;Kol et al, 2017;Sveinsdottir et al, 2016), retention and intent to quit (Dawson et al, 2014;Özer et al, 2017), nurse outcomes (Hahtela et al, 2015), and patient outcomes including safety and quality care (Chiang et al, 2017). Aiken et al (2011) conducted a large international study involving nurses from 1,406 hospitals over a 10-year period (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to countries in North America, countries identifying workplace environment as an area of interest included, but were not limited to: Australia, Estonia, Finland, Hong Kong, Iceland, Israel, Turkey, and Taiwan. Topics addressed in selected publications included job satisfaction (Chien & Yick, 2016;Dekeyser Ganz, & Toren, 2014;Jiang et al, 2016;Kaunonen et al, 2015;Kol et al, 2017;Sveinsdottir et al, 2016), retention and intent to quit (Dawson et al, 2014;Özer et al, 2017), nurse outcomes (Hahtela et al, 2015), and patient outcomes including safety and quality care (Chiang et al, 2017). Aiken et al (2011) conducted a large international study involving nurses from 1,406 hospitals over a 10-year period (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a study conducted in Turkey showed that the promotion system was based on personal relationships rather than merit, which negatively affected workforce productivity (Dikmen et al., 2016). Another study, in which positive work environment and management strategies were implemented, stated that one of the parameters where nurse satisfaction rates significantly increased was ‘merit‐based recruitment and promotions’ (Kol et al., 2017). McCallin and Frankson (2010) reported that having inadequate management skills in nurse managers' appointments caused significant problems in their executive roles.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that nurse managers' business management and leadership skills were inadequate despite their expanding roles (Mancuso, 2016; McCallin & Frankson, 2010). In addition, some studies have mentioned that nursing appointments and promotion systems are based on personal relationships rather than a merit‐based system, adversely affecting workforce productivity (Dikmen, Kara Yılmaz, Başaran, & Filiz, 2016), and nurses are not satisfied with these assignments (Kol, İlaslan, & Turkay, 2017). Another study by Cleary, Horsfall, Muthulakshmi, Happell, and Hunt (2013) showed that nurses experienced constraint in receiving further training based on allowances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemşirelerin kurumdan ayrılma nedenleri incelendiğinde kariyer gelişiminin olmaması, ücret azlığı, yapılan işe göre ek ödemenin azlığı, hasta/hemşire oranlarının yüksek olması ve nöbet sayılarının fazlalığı gibi çalışma ortamının özelliklerine ilişkin faktörler olduğu gösterilmiştir (5,6). Motive edici ve destekleyici olumlu bir çalışma ortamının hemşirelerin memnuniyetini, iş doyumunu ve kariyer başarısını artırdığı, hemşireleri kurumda tutmayı sağladığı ve devir hızını düşürdüğü pek çok çalışma sonucuyla gösterilmiştir (7)(8)(9)(10). Bunların yanı sıra olumlu çalışma ortamının yeni mezun hemşirelerin yetkinliğini, memnuniyetini arttırdığı ve kurumda kalmasını sağladığı da vurgulanmaktadır (11).…”
unclassified